A4NH 2019 annual report highlights: Gender - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2020)
This includes three highlights document for the Gender flagship of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Impact of pro-WEAI grows Highlight 2: Empowering new veterinarians in Malawi to incorporate gender and equity in their work Highlight 3: Analyzing equity in agriculture, nutrition, and health research